A fluid–structure interaction analysis of anisotropic Dacron fabric used for aortic replacement. (August 2020) - Jayendiran, Raja; Nour, Bakr; Ruimi, Annie
Abstract: We present the results of a computational study aimed at capturing the behavior over time of Dacron fabric used for surgical correction of aortic aneurysms. The study concerns the problem of compliance mismatch between the graft and the native aorta and is very important to clinicians. The aorta is represented by a sophisticated anisotropic hyperelastic model (GOH), which takes into account the orientation of the collagen fibers. The corrugations present on the Dacron fabric are modeled geometrically using experimental data retrieved from the literature. The viscoelastic behavior of the Dacron graft reported by clinicians is also taken into account. Mechanical quantities experienced by the graft sewn to an aortic segment are obtained using fluid–structure interaction (FSI) simulations assuming realistic blood flow conditions. Both ascending and descending aorta with two curvatures are considered. Results of this study indicate that (i) the strains on the Dacron-aorta structure increase with increasing curvature and over time (ii) the simulations are capable of capturing stress concentrations at the junction of the graft and the aorta and (iii) the wall shear stresses (WSS) are substantially higher on the aortic segment than on the Dacron graft.